Afrosystolederus garmsi (Orthoptera, Tetrigidae), a new genus and species from Mount Gibi (Liberia) with remarks on Systolederus, Pseudosystolederus and Teredorus - Devriese, Hendrik; Husemann, Martin (Zootaxa, 2023)
A new genus, Afrosystolederus, and a new species, Afrosystolederus garmsi, are described from Mount Gibi in Liberia. This African genus is most similar to Pseudosystolederus Günther, 1939 from Africa and Madagascar and to some members of Systolederus Bolivar, 1887 from Asia. The taxonomic difficulties of genera and species with a narrow fastigium are discussed. Teredorus aztecus nov.comb. is transferred from the genus Paratettix Bolivar, 1887. It is proposed to transfer all Indo-Malayan species from Teredorus Hancock, 1907 to Systolederus Bolivar, 1887, resulting in 26 new combinations and six replacement names: Systolederus albimarginus (Zheng & Zhou, 1996) nov. comb., Systolederus bashanensis (Zheng, 1993) nov. comb., Systolederus bhattacharyi (Shishodia, 1991) nov. comb., Systolederus bidentatus (Zheng, Huo & Zhang, 2000) nov. comb., Systolederus bipulvillus (Zheng, 2006) nov. comb., Systolederus brachynotoides Zheng, Ou & Lin, 2012 nov. comb., Systolederus brachynotus (Zheng & Xu, 2010) nov. comb., Systolederus camurimarginus (Zheng, 1998) nov. comb., Systolederus carmichaeli (Hancock, 1915) nov. comb., Systolederus chiangraensis (Za, Wen, Kang & Hyde, 2016) nov.comb., Systolederus combfemorus (Za, Wen, Kang & Hyde, 2016) nov. comb., Systolederus ebenotus (Zheng & Li, 2001) nov. comb., Systolederus eurylobatus (Zheng, Shi & Mao, 2010) nov. comb., Systolederus flatimarginus (Zheng & Liang, 2000) nov. comb., Systolederus flavistrial (Zheng, 2006) nov. comb., Systolederus frontalis (Hancock, 1915) nov.comb., Systolederus guizhouensis (Zheng, 1993) nov. comb., Systolederus hainanensis (Zheng, 1993) nov. comb., Systolederus longipulvillus (Zheng, 1988) nov. comb., Systolederus nigropennis (Deng, Zheng & Lu, 2013) nov. comb., Systolederus parvipulvillus (Deng, Lei & Zheng, 2014) nov. comb., Systolederus prominemarginis (Zheng & Jiang, 1993) nov. comb., Systolederus taibeiensis (Zheng & Xu, 2010) nov. comb., Systolederus xishuiensis (Zheng, Li & Shi, 2003) nov. comb. , Systolederus wuyishanensis (Zheng, 1993) nov. comb., Systolederus lii Devriese nov. nom., Systolederus lini Devriese nov.nom., Systolederus oui Devriese nov. nom., Systolederus rongduensis Devriese nov. nom., Systolederus yuanlingensis Devriese nov. nom., Systolederus zhengi Devriese nov. nom.